A rapid enzymatic DNA sequencing technique: determination of sequence alterations in early simian virus 40 temperature sensitive and deletion mutants. - Seif, I (1980)
We have adapted a rapid sequencing technique from the enzymatic nick-translation method of Maat and Smith. The Forward-Backward procedure employs both synthetic and 3' to 5' exonucleolytic activities of E. coli DNA polymerase I to achieve greater reliability, especially in reading stretches of the same nucleotide. The technique has been employed to determine sequence alterations in four early SV40 temperature-sensitive (tsA) point mutants and five early SV40 viable deletion mutants. The nucleotide sequence of these mutants provides an insight into their biological properties.